Influencia de los ingresos, las utilidades, los pasivos, el patrimonio, el apalancamiento, la volatilidad, el riesgo y la liquidez de una acción en el rendimiento anual de las acciones de las empresas más representativas del COLCAP en Colombia (2020)
People who invest in Stock Exchanges have many markets in which they can participate depending on their main objective. In this way, they must understand the characteristics that each market has in order to make the right decisions. That is why the purpose of this study is to understand the characteristics of the Stocks, explaining the influence of incomes, profits, debt, equity, leverage, volatility, risk and volume on the annual stock returns of the Colombian COLCAP index most important companies. This tesis is important because the other investigations that have been done all around the world try to explain the relation between these economic variables but not when they appear at the same time. That is why the main objective of this study is to develop a statistical data panel fixed effect model which shows us the simultaneous relations between these variables. The most important conclusion of this investigation is that the variables that explain the change on the stock returns of the companies that we studied are: incomes, equity, volume and debt; highlighting that incomes, equity and volume have a positive impact and debt has a negative impact.